Importancia De Los Diluyentes Para La Conservación Y Preservación En Semen Equino (2023)
Equine semen refrigeration is an assisted reproduction technique that has been increasingly used and developed in recent years, as it allows semen to be stored and transported while maintaining its potential fertility for around 24 hours. Extenders have been established as an alternative to compensate for the problems that occur during the conservation or preservation of equine semen, since various molecules with antioxidant properties can be added to them. Different semen refrigeration extenders have been developed to ensure that the sperm maintains its qualities for a fertilizing ejaculate, there are currently a large number of commercial extenders based on different elements and thus achieve adequate sperm preservation. The optimization of these seeks to guarantee the maximum possible viability and fertility of the semen (Ribeiro et al., 2015).